Revisiting port sustainability as a foundation for the implementation of the United Nations Sustainable Development Goals (UN SDGs) - Anas S. Alamoush; Fabio Ballini; Aykut I. Ölçer (Journal of Shipping and Trade (JST), 2021)
Port sustainability studies are increasing rapidly and are skewed toward environmental aspects, while at the same time their results are fragmented, making it difficult to collectively assess conclusions. This study, therefore, aims at building a framework which categorises port actions, measures, and implementation schemes (policy tools to improve the uptake), utilising the critical literature review method. Additionally, linkage of port sustainability to the United Nations' Sustainable Development Goals (UN SDGs) is highlighted. Port sustainability includes internal (port side) and external (ships and land transport) actions and measures. The study results form 16 homogeneous and interconnected sustainability categories, including a non-exhaustive list of operationalising measures, encompassing the three dimensions of sustainability (environment, economy and society) while implementation schemes are divided into four groups. Considering that ports are under scrutiny and perceiving growing pressure to improve their sustainable pathways, for example by addressing climate change and energy consumption, the identified ports' sustainability actions and measures, including the linkage with the UN SDGs, are overarching and multidimensional and seen as a step in achieving far-reaching sustainable implementation. The study's practical implications guide port policymakers and industry practitioners to go beyond the low hanging fruit (customary practices), and enable them to take reliable decisions for broader sustainability implementation. Additionally, the identified research implications stimulate further academic discussions.
Keywords: 650; Actions and measures; Implementation; Ports; Sustainability; TBLs; Triple bottom lines; UN SDGs